Model Pelayanan Kontekstual Kiai Sadrach Dalam Pekabaran Injil di Tanah Jawa - Suranto Suranto; John Abraham Christiaan (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2022)
The basis of this research is the interest of researchers in the development of Christians in java which is so rapid until now, which is said to have originated from local indigenous gospel preachers who had not previously believed in Christ, but later became a very bitter person in the spread of Christianity in Java. One of the important figures in the development of Christian teaching in Java is inseparable from the role of a man named Radin, who later became Radin Abas and after being babtis became Kiai Sadrach. The development of Javanese Christianity is part of the unique and interesting way of ministry of Kiai Sadrach, because his risky way of arguing and his strong beliefs made him win in every debate so that many people have become believers in the gospel of Christ in Java until today. The method used in this paper is qualitative with a literature study approach. The contextual service model carried out by Radin Abas aka Kiai Sadrach is very memorable and acceptable to the local people of Java, especially Central Java. As a result, Christianity in Java has grown rapidly until now, even then Kiai Sadrach was named the Apostle of Java.